HUBUNGAN FUNGSI AFEKTIF KELUARGA DENGAN PERILAKU KENAKALAN REMAJA - Elza ' Mursafitri; Herlina ' '; Safri ' ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Adolescent is a period where there is a transition childhood to adulthood. Psychological development task of adolescent is identity search. If teenagers are not able to search for identity would cause a negative impact such as juvenile delinquency. External factor causing juvenile delinquency one of which is the family. The purpose of this research is to determine the relationship between the affective functioning of the family with juvenile delinquency behavior in SMKN 2 Pekanbaru with descriptive correlation of research design and cross sectional approach. The sample of this research are 341 respondents were taken based on inclusion criteria using probability sampling technique with the type of stratified random sampling. The measuring instrument used is a questionnaire. The analysis used univariate analysis to determine the frequency distribution and bivariate analysis using chi-square test. The results showed that the 170 respondents had affective functioning of the family of inadequately, 105 respondents have higher juvenile delinquency behavior (30.5%) and 65 respondents have lower juvenile delinquency behavior (19.1%). From 171 respondent had an affective functioning of the family of adequate, 105 respondent have lower juvenile delinquency behavior (30.8%) and 66 respondent have higher juvenile delinquency behavior (19.4%). Based on result of chi-square test obtained of p-value (0.000) < alpha (0.05), so that there are significant relationship between the affective functioning of the family with behavior of juvenile delinquency. Based on this study recommended to families with adolescent to improve affective functioning of the family in an effort to prevent and reduce juvenile delinquency behavior. Keywords: Adolescent, affective functioning of the family, juvenile delinquency behavior